Immunomodulatory Activity of Enau (Arenga pinnata) Leaf Extract on Macrophage Phagocytosis in Mice - Yuliastri, Wa Ode; Sahidin, Idin; Isrul, Muhammad; Setiawan, La Ode Wawan (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
The immune system is vital in protecting the body from pathogens and harmful foreign substances. This study aims to evaluate the immunomodulatory activity of Arenga pinnata leaf extract on macrophage phagocytosis activity in mice (Mus musculus) and determine its optimal dosage. Extraction was conducted using the maceration method with 96% ethanol as the solvent. The immunomodulatory test was performed by measuring macrophage phagocytosis activity. Male mice were divided into six groups: a negative control (0.5% Na-CMC), a positive control (Stimuno® 0.013 mg/kgBW), and four treatment groups receiving Arenga pinnata leaf extract at doses of 100 mg/kgBW, 200 mg/kgBW, 300 mg/kgBW, and 400 mg/kgBW. After seven days of treatment, the mice were injected intraperitoneally with Staphylococcus aureus bacteria, and peritoneal fluid was collected for macrophage phagocytosis activity analysis under a microscope. The results showed that Arenga pinnata leaf extract significantly increased macrophage phagocytosis activity at 300 mg/kgBW and 400 mg/kgBW compared to the positive control. Phytochemical analysis revealed the presence of flavonoids, saponins, tannins, and triterpenoids, which contribute to its immunomodulatory effects. In conclusion, Arenga pinnata ethanol leaf extract exhibits potential as an immunomodulatory agent, particularly at 300 mg/kgBW and 400 mg/kgBW doses. However, further studies are necessary to explore its pharmaceutical applications and elucidate its mechanisms of action.